Effects of Various Physical Interventions on Reducing Neuromuscular Fatigue Assessed by Electromyography: A Systematic Review and Meta-Analysis - Hou, Xiao; Liu, Jingmin; Weng, Kaixiang; Griffin, Lisa; Rice, Laura A.; Jan, Yih-Kuen (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: Various interventions have been applied to improve recovery from muscle fatigue based on evidence from subjective outcomes such as perceived fatigue and soreness, which may partly contribute to conflicting results of reducing muscle fatigue. There is a need to assess the effectiveness of various intervention on reducing neuromuscular fatigue assessed by a quantitative outcome such as electromyography (EMG). The objective of this review and meta-analysis was to evaluate the effectiveness of different interventions and intervention timing for reducing fatigue rates during exercise. Methods: The literature was searched from the earliest record to March 2021. Eighteen studies with a total of 87 data points involving 281 participants and 7 types of interventions (i.e. active recovery, compression, cooling, electrical stimulation, light emitting diode therapy, massage, and stretching) were included in this meta-analysis. Results: The results showed that compression (SMD=0.28; 95%CI= -0.00 to 0.56; P=0.05; I2=58%) and light emitting diode therapy (SMD=0.49; 95%CI= 0.11 to 0.88; P=0.01; I2=52%) have a significant recovery effect on reducing muscle fatigue. Additionally, compression, active recovery, and cooling have a significant effect on reducing muscle fatigue when conducted during exercise, while a non-effective trend when applied after exercise. Discussion: This meta-analysis suggests that compression and light emitting diode therapy have a significant effect on reducing muscle fatigue. The results also suggest that there is a significant effect or an effective trend on reducing muscle fatigue when compression, active recovery, cooling, and electrical stimulation are applied during exercise, but not after exercise.